Analisis Manajemen Risiko dalam Pembiayaan Murabahah pada PT. BPRS Baiturrahman di Aceh Besar - Mukhlis Mukhlis (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2021)
This study aims to determine the Murabahah Financing Risk Management Procedure, implementation of Murabahah Financing Risk Management, Impact of the Implementation of Murabahah Financing Risk Management and How to Implement Murabahah Financing Risk Management from the Perspective of Islamic Economic Law. This study used a descriptive qualitative design. Research data obtained from surveys, interviews and documentation studies. The data analysis used descriptive techniques, the implementation of which was carried out in three stages, namely the data reduction stage, the display stage (data grouping), and the verification stage. The results showed that the Murabahah Financing Risk Management Procedure implemented by PT. BPRS Baiturrahman is very concrete and detailed and serves as a reference in the Murabahah financing process. Murabahah Risk Management Implementation at PT. BPRS Baiturrahman uses the principle of prudence with a factor of 5 C, namely Character, Capacity, Capital, Colleteral and Condition. The implementation of Murabahah Financing Risk Management did not run optimally, this can be seen from the increase in the NPF of murabahah financing. Implementation of Financing Risk Management based on the Perspective of Islamic Economic Law, in general the implementation of risk management for murabahahah financing at PT. BPRS Baiturrahman pays close attention to provisions related to implementation in accordance with applicable sharia principles including Fatwa DSN-MUI No.04 / DSN-MUI / IV / 2000 in its implementation being supervised by the Dewan Pengawas Syariah